Spatialized Pedagogy: Adapting Non-Formal Education Strategies for Stunting Prevention in Mountainous Regions - Ningsih, Yuyun Setia; Wahyudi , Adib (CV Bumi Spasial, 2025)
Stunting is not merely a nutritional deficit but often a consequence of low spatial-health literacy in marginalized communities. This study evaluates the Family Hope Program (PKH) in Giripurno Village, Batu City, positioning it as a non-formal geographic education intervention. While the village faces high stunting rates, its mountainous topography creates distinct